PELATIHAN TARI ANAK-ANAK SEBAGAI DASAR BELAJAR TARI TRADISI DI SANGGAR SENI TRADISIONAL KRIDO BUDOYO SILIR, KEL. SEMANGGI, KEC. PASAR KLIWON KOTA SURAKARTA - Mamik Widyastuti (Institut Seni Indonesia Surakarta, 2019)
Sanggar Seni Tradisi Kridho Budoyo which available in Silir, Semanggi urban village, which is now located at Rusnawa Silir downstairs, and located east of Silir Semanggi chicken market. This Sanggar was always serving the underprevileged children, that is children of artisans, scavengers, and riskhaw pullers. Grants interve to see the situation of the Sanggar. At first, the Sanggar builded by Wahyudi Widodo, and what makes him inspired to establish to the Sanggar is based on the concerns of children who likes to playwhich does not yet have a place to play activities officially. Sanggar Seni Tradisi Kridho Budoyo given SK with Number 431.i/0992/SBSP/VI/2011 dari Dinas Kebudayaan dan Pariwisata Suirakarta.Sanggar Seni Tradisi Kridho Budoyo was born of the concern to nurture,ccomodate and channel the talents of young generation in the field of art, especially dance art.Keywords: Studio, dance , training, Krido Budoyo.